Two Dimensional Thermal-Hydraulic Analysis for a Packed Bed Regenerator Used in a Reheating Furnace - Chien-Nan Lin; Jiin-Yuh Jang; Yi-Shiun Lai (Energies, 2016)
Packed bed is widely used for different industries and technologies, such as heat exchangers, heat recovery, thermal energy storage and chemical reactors. In modern steel industry, packed bed regenerator is widely utilized in the reheating furnace to increase the furnace efficiency. This study established a two dimensional numerical model to simulate a packed bed used in regenerative furnaces. The physical properties of fluids and packed stuffing (such as density, thermal conductivity, and specific heat) are considered as functions of temperature to adapt the large temperature variation in operation. The transient temperature profiles of the flue gas, packed bed, and air during the heating and regeneration period are examined for various switching time (30, 60, 120, and 240 s). The results reveal that, during the heating period, the spanwise averaged heat transfer coefficient is decreased along the longitudinal downstream direction, while during the regeneration period, the opposite trend is true. Moreover, the regenerator thermal effectiveness is decreased by increasing the switching time.